Why We Can't Help but Call Ourselves (All) ‘Sartorians’ - Marco Giuliani (Italian Political Science, 2025)
This article, presented at the Annual Conference of the Italian Society of Political Science in 2024, explores the intellectual legacy of Giovanni Sartori and his enduring influence on political science. The author reflects on Sartori’s contributions to three key domains: political theory, methodology, and comparative politics. The text highlights Sartori’s insistence on theory-driven approaches over purely data-centred methods, as well as his critical stance on the behavioural drift of social sciences. The article also underscores Sartori's dedication to bridging theory and practice, advocating for political science as a tool for addressing real-world challenges. In conclusion, it calls for greater public engagement within the discipline, proposing initiatives like a political science festival to further Sartori’s vision of a socially impactful academic field.